Analisis Kebutuhan Pasien pada Pelayanan Kefarmasian di Klinik Rawat Jalan RSUD dr. Soebandi Jember: Studi Kasus Layanan Resep - Zora Olivia; Umi Athijah; Wahyu Utami (Fakultas Farmasi Universitas Pancasila, 2019)
The aim of this research was to know the drug related need in the pharmacy service atpharmacy special prescription service. Descriptive study was done to out patient who fulfi ll prescriptionin the pharmacy Dr Soebandi Jember Hospital. A sample of this population is 557 patients taken withsampling techniques with stratifi ed random sampling. Retrieval of data in this study using a questionnaireinstrument. From the data needs of the patient at the pharmacy pharmacy services in the majority ofpatients explain need to therapy appropriate treatment indication for 85.6 %, at eff ective 84.9 %, atsafely 77.4 % and can be used according to the rules of use of 94.4 %. Based on these data it can beconcluded that the needs of patients at the pharmacy services are appropriate indications, eff ective,safe and can be used according to the rules of use. The requirement can be achieved due to appropriatepharmacy services running and providing pharmaceutical care is a pharmacist. Reimbursements arereimbursed by the insurance company should not be given to Pharmacist Pharmacy for pharmaceuticalcare can not walk if no pharmacist.